SEASONAL VARIATIONS IN ANTIBIOTIC CONSUMPTION IN PAEDIATRIC PRIMARY CARE SETTINGS IN SERBIA. Issue 1 (14th December 2015) - Božić, Bojana; Bajčetić, Milica
Abstract : Background/Objective: Antibiotics are the most irrational prescribed drugs among the paediatric population. The aim of this study was to evaluate the seasonal variations in antibiotic prescribing profile among children in primary care settings in Serbia. Methods: Prescriptions of systemic antibiotics to the paediatric population (<18 years) for the period between 2011 and 2013 were analyzed by using the National Health Insurance Fund's outpatient reimbursement database. Results: The average number of antibiotic prescriptions was 1.887.615, while the average number of children receiving antibiotics was 728.285. The average annual rate was 1.394 antibiotic prescriptions per 1000 children. Significant differences in prescription rates in winter months compared to summer months were observed (t=5.51 p<0.001; t=2.29 p=0.045; t=3.65 p=0.004 for 95% confidence interval) during the followed up period. The average annual prevalence of antibiotic prescriptions was 54%. The most commonly prescribed antibiotics in paediatric population were amoxicillin, amoxicillin/clavulanic acid, cephalexin, azithromycin and erythromycin (90% of all prescribed antibiotics). The highest percentage of prescribed antibiotics was observed in the group of 2- to- 23- months-old children. Broad spectrum penicillins were the most prescribed antibiotics in all age groups, especially for children from 2–11 years of age, 51.92% (44.90%–57.13%), while the rate for cephalosporins was highest for children from 2–23 months, 30.91% (26.38%–36.44%), macrolides from 12 to 18 years, 22.67% (19.79%–26.05%) and quinolones from 0–1 month of age, 6.64% (5.09%–9.52%). Conclusions: Significant seasonal variations in prescription practice and frequently used broad-spectrum antibiotics indicate that antibiotic prescribing is inappropriate.